The relationship between family-focused organisational and supervisor support and positive work-outcomes - Mohasi, Mapalo (Organisational Psychology, 2015)
This study examined the relationship between family-focused organisational and .supervisor support and the positive work outcomes, job satisfaction, affective commitment, continuous commitment and work-family enrichment.